Legal Analysis of BPOM Supervision of Illegal Cosmetic Product Distribution: A Case Study of Reza Gladys Products - Yuliana Munthe (Universitas Negeri Semarang, 2026)
This study aims to analyze the effectiveness of supervision conducted by the Food and Drug Supervisory Agency (BPOM) on the distribution of illegal cosmetics in Indonesia through a case study of products marketed by Reza Gladys. The rampant circulation of illegal cosmetics, particularly through digital platforms and social media, indicates challenges in ensuring business operators' compliance with product safety, quality, and legality standards in accordance with statutory regulations. This study uses a normative juridical method with a regulatory and conceptual approach to examine BPOM's pre-market and post-market supervision mechanisms and the obligations of business actors in obtaining distribution permits before marketing products. The results of the study indicate that the distribution of cosmetics without distribution permits has the potential to pose risks to consumers because they do not undergo a safety evaluation process and do not provide accurate information about their composition or how to use them. A case study of products marketed by Reza Gladys shows violations in the form of a lack of distribution permits and marketing practices that have the potential to mislead consumers. Therefore, strengthening digital supervision, law enforcement, and inter-agency coordination is necessary to improve legal protection for consumers.